Recent Referees (Journal of Political Economy, 2019)
Previous articleNext article FreeRecent RefereesPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreJournal of Political Economy acknowledges the assistance of:Ran AbramitzkyEliot AbramsDaron AcemogluPhilipp AgerMohammad AkbarpourDouglas AlmondIsaiah AndrewsCharles AngelucciEduardo AzevedoScott BakerMiguel BallesterSamuel BazziJere BehrmanManudeep BhullerBruno BiaisDan BlackAlessandro BonattiMichael BordoEthan Bueno de MesquitaAriel BursteinLeonardo BursztynMarika CabralSteven CallanderJuan CarrilloKatherine CaseyAllan Collard-WexlerJonathan ColmerThomas CovertBenjamin CrostGordon DahlAndrew DaughetyGustavo De SouzaMelissa DellRebecca DiamondMichael DicksteinWill DobbieUlrich DoraszelskiChristian DustmannPiotr DworczakBenjamin EdelmanLasse EikaIgnacio EspondaJianqing FanHanming FangMax FarrellShuaizhang FengJesus Fernandez-VillaverdeJoseph FerrieFrederico FinanChristopher FlinnMarco FrancesconiPatrick FrancoisChao FuXavier GabaixPatrick GagliardiniCraig GalletOded GalorJorge Luis GarciaCamilo Garcia-JimenoMatthew GentzkowAlexander GorbenkoPiero GottardiJoshua GottliebFrancois GourioJeff GroggerRaymond GuiterasMarcus HagedornWilliam HanlonChiaki HaraTarjei HavnesKen HendricksRandi HjalmarssonRichard HoldenRichard HornbeckPeter HullSonia JaffePhilippe JehielGinger JinAmir JinaMatthew KahnRohan KekreRyan KelloggWilliam KerrBen KeysMartin KliemPatrick KlineScott KominersYunmi KongWojciech KopczukIgor KopylovBotond KoszegiTom KrebsKory KroftFelix KublerPeter KuhnKevin LangFabian LangeKurt LavettiJacob LeshnoMartin LettauEdwin LeuvenAndrei LevchenkoShengwu LiTong LiMing-Jen LinMaarten LindeboomJohn ListAlessandro LizzeriKatrine LokenGuido LorenzoniJune MaJim MacGeeNeale MahoneyMihai ManeaAlan ManningGustavo MansoRamon MarimonGiovanni MastrobuoniNiko MatouschekKathleen McGarryAlisdair McKayBrian McManusJonathan MeerLeonardo MelosiKyle MengMoritz Meyer-ter-VehnGuy MichaelsEdward MiguelKurt MitmanMassimo MorelliThayer MorrillMichael Mueller-SmithCaitlin MyersBarry NalebuffDerek NealPeter NormanMichael OstrovskyThomas PalfreyAmanda PallaisRohini PandeFernando ParroMichael PetersHerakles PolemarchakisBruce PrestonGautam RaoDaniel RappoportJohn RehbeckLudovic RenouHelene ReySteven RivkinJames RobertsJean-Laurent RosenthalMark RosenzweigHeather RoyerAysegul SahinBernard SalanieAnalia SchlosserMoritz SchularickKarl SchurterJoseph ShapiroBradley ShapiroHolger SiegArunima SinhaLones SmithAnthony Smith, Jr.Erik SnowbergPaulo SomainiJorge SpenkuchCharles SprengerLudwig StraubJohannes StroebelJan StuhlerTakuo SugayaPaolo SuricoJustin SydnorBalazs SzentesPietro TebaldiFelix TintelnotJean TirolePetra ToddAlexander TorgovitskyAaron TornellRagnar TorvikUtku UnverMartin UribeArthur van SoestAdrien VerdelhanPietro VeronesiJonathan VogelNico VoigtlaenderFabian WaldingerReed WalkerThomas WinberryAlexander WolitzkyLeeat YarivJunjian YiAli YurukogluBasit Zafar Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 127, Number 5October 2019 Article DOIhttps://doi.org/10.1086/706773 © 2019 by The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.